The Islamic hedging management: Paving the way for innovation in currency options - Nordin, Nadhirah; Hashim, Hydzulkifli (Universiti Utara Malaysia, 2014)
Islamic hedging is one of the most important tools for risk management.Currency options contracts are commonly regarded as one of the useful tools of risk management and frequently used to reduce risk associated with the movement in price and currency risk.This article attempts to review the suitability of the Islamic currency options in one of the Islamic banks in Malaysia as a hedging mechanism and highlights Shariah issues pertaining to the structures.Currency options are prohibited in Islamic finance due to the issue of riba and to the violation of the bay al-sarf rule which requires currency trading to be done on “spot” basis only. Options contract is also rejected by some scholars because of premium payment or chargeable fees to the right. In view of the overwhelming importance of currency risk management in the volatile market, the application of Shariah principles in currency market faces a great challenge to Islamic scholars today. Based on the observation of the bank’s official information disclosed to the public and the interview conducted, the finding of this research indicates that the bank permitted currency options based on the principle of tawwaruq (commodity murabahah) or bay al-inah and wa’ad (unilateral promise) which are strictly used for hedging purposes.Tawwaruq and wa’ad principles have given Islamic financial institutions the opportunity to structure Shariah compliant financial products and meet the objective of increasing trading volume and liquidity in order to reduce transaction cost and risk.